Atlas of microstructures of constructional materials study aid - Egorov specialist in mechanical engineering The Head of the Laboratory of Tomsk Polytechnic University, candidate of technical Sciences; Strelkova Specialist in the field of material science Associate Professor of Tomsk Polytechnic University, Candidate of technical sciences; Khvorova specialist in the field of materials science Senior Lecturer of Tomsk Polytechnic University; Baginski specialist in the field of material science senior lecturer of Tomsk Polytechnic University (Tomsk Polytechnic University Publishing House, 2019)
The atlas of microstructures is a set of photographs of microstructures with descriptions and reference data for study the "Materials Science", the discipline of professional cycle. The Atlas of Microstructures includes such groups of materials as carbon steels, cast iron, non-ferrous metal alloys. The manual is intended for students learning in the direction of 15.03.01 "Mechanical Engineering".